PENGARUH KOMPENSASI DAN PENGEMBANGAN KARIER TERHADAP RETENSI KARYAWAN PADA PERUMDA AIR MINUM TIRTA LATIMOJONG (PAMTL) KABUPATEN LUWU - Rahmat, A. Syech; Tahier, Ilham; Duriani, Duriani (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
This study aims to investigate the influence of compensation and career development on employee retention. Data were collected through questionnaire distribution using the Likert scale. The population consisted of employees from the Regional Water Utility Company Tirta Latimojong (PAMTL) in Luwu Regency. The variables studied included compensation and career development as dependent variables, and employee retention as the independent variable. The results indicate that both compensation and career development have a positive and significant impact on employee retention. This research contributes to understanding the factors influencing retention in the context of organizational management and provides insights for enhancing employee engagement and longevity within the organization.